Conductive composites of natural rubber and carbon black for pressure sensors - Job, A. E.; Oliveira, F. A.; Alves, Neri [UNESP]; Giacometti, J. A.; Mattoso, LHC (Elsevier B.V., 2003)
Composites of natural rubber and carbon black have attracted great interest due to their technological applications. In this work natural rubber (NR) and carbon black (CB) were compounded, aiming the development of composites with good mechanical properties, processability and electrical conductivity for use as pressure sensors. The electrical conductivity changes from 10(-11) to 10(-2) S.cm(-1) depending on the percentage of CB in the composite. It was also observed that the conductivity varies reversibly and linearly with the applied pressure. The latter demonstrates that this material can be used as pressure sensors.
Keywords: natural rubber; carbon black; composites; pressure sensor